Początki ruchu demokratycznego w Chińskiej Republice Ludowej (1976-1981) - Bartolik, Jakub (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
China is an emerging superpower. Its economical strength contrasts the lack of free speech and other liberties crucial for a prosperous economy. The democratic opposition is almost in its demise and society has little interest in politics. However, it hasn’t always been like that. This paper shows how the democratic movement emerged and it has developed since the mourning over the death of prime minister Zhou Enlai in 1976 during the Qing Ming, or the Tomb Sweeping festival. It also focuses on the intellectual turmoil of the Wall of Democracy in 1978, where some of the most important dissidents were published. This Chinese Hyde Park was officially closed in 1979 as the wave of repressions hit the dissidents. That event became a solid foundation for the future democratic opposition.